Pengelolaan Air Limbah pada Proyek Konstruksi: Tinjauan Sistem Zero Liquid Discharge - Baso, Darwis; Thariq, Jabbar (Universitas Tanjungpura, 2026)
Wastewater management in construction projects is a strategic issue in supporting sustainable development. The Zero Liquid Discharge (ZLD) system has emerged as an innovative solution to eliminate liquid effluents through water recovery and solid utilization. This study employs a literature review approach, covering scientific publications from 2016–2025, to identify the efficiency, technical challenges, and policy implications of ZLD implementation in the construction sector. The findings show that ZLD can recover 85–98% of wastewater, producing water that meets reuse standards for non-potable purposes such as equipment cleaning, concrete curing, and dust suppression. System efficiency is influenced by wastewater characteristics, technological configuration, and energy sources, with specific energy consumption ranging from 5 to 12 kWh/m3. Life Cycle Assessment (LCA) analysis indicates that ZLD reduces water pollution by up to 95%, but may increase carbon emissions by around 20% if low-carbon energy is not used. Strategically, ZLD integration requires supportive green policies, sustainable financing, and the adoption of circular-economy principles to accelerate the transition to green construction.